Preparation of organic–inorganic nano-composites for antireflection coatings - Chen, Ching-Chung; Lin, Dar-Jong; Don, Trong-Min; Huang, Feng-Hsi; Cheng, Liao-Ping (Journal of non-crystalline solids, 2008)
In this research, bi-layer thin film stacks that served as an antireflective coating were developed. The top layer was synthesized using tetraethoxysilane and 3-(trimethoxysilyl) propyl methacrylate by the well-known sol–gel technique. Its refractive index was lower than that of the bottom layer, which was prepared by reaction between tetrabutoxyltitanium and γ-glycidoxy propyl trimethoxysilane. Antireflective coatings were obtained by spin-coating of the synthesized sols on a glass substrate, followed by pre-drying, UV-curing, and post-baking. Fourier transform infrared spectrometer was employed to investigate the evolution of chemical bonds during the UV-curing and the sol–gel processes. The size of the inorganic/organic hybrid particles in the sol was found to be less than 10 nm, as measured by transmission electron microscope and dynamic light scattering. Thermo gravimetric analyzer was used to find out the thermal degradation temperature of the two layers and the effect of post-baking. The results indicated that the thermal stability increased after post-baking at 200 °C for 15 min. The reflectance of the antireflection coating was controlled by the relative refractive indices and the thickness of the top and bottom layers. Under optimal synthesis condition, we obtained an antireflection coating, exhibiting a low reflection, 1% at 550 nm, in the visible range.